Chitosan as a Templating Agent of Calcium Phosphate Crystalline Phases in Biomimetic Mineralization: Theoretical and Experimental Studies - Stafin, Krzysztof; Śliwa, Paweł; Pia Tkowski, Marek; Matýsek, Dalibor (ACS applied materials & interfaces, 2024)
Highlighting the essential role of chitosan (CS), known for its biocompatibility, biodegradability, and ability to promote cell adhesion and proliferation, this study explores its utility in modulating the biomimetic mineralization of calcium phosphate (CaP). This approach holds promise for developing biomaterials suitable for bone regeneration. However, the interactions between the CS surface and in situ precipitated CaP still require further exploration. In the theoretical section, molecular dynamics (MD) simulations demonstrate that, at an appropriate pH level during the prenucleation stage, calcium ions (Ca2+) and hydrogen phosphate ions (HPO42-) form Posner-like clusters. Additionally, the interaction between these clusters and the CS molecule enhances system stability. Together, these phenomena facilitate the transition to subsequent heterogeneous nucleation on the surface of the organic matrix, which is a more controlled process than homogeneous nucleation in solution. Dynamic simulation results suggest that CS acts as a stabilizing matrix at pH 8.0 during biomimetic mineralization. In the experimental section, the effects of pH and the molecular weight of CS were investigated, with a focus on their impact on the crystal structure of the resulting material. X-ray diffraction and scanning electron microscopy analyses reveal that, under conditions of approximately pH 8.0 and a CS molecular weight of 20 000 g/mol, and controlled ion concentration, ultrasound radiation, and temperature, the dominant CaP phases in the material are carbonate-doped hydroxyapatite (CHA) and octacalcium phosphate (OCP). These findings suggest that CS, when adjusted for molecular weight and pH, facilitates the formation of CaP crystal phases that closely resemble the natural inorganic composition of bone, highlighting its protective and regulatory roles in the growth and maturation of crystals during mineralization. The theoretical predictions and experimental outcomes confirm the crucial role of CS as a templating agent, enabling the development of a biomimetic mineralization pathway. CS's ability to guide this process may prove valuable in the design of materials for bone tissue engineering, particularly in developing effective materials for bone tissue healing and regeneration.
Keywords: carbonate-doped hydroxyapatite; Crystallization; Calcium Phosphates; simulace molekulární dynamiky; biomimetické materiály; krystalizace; molecular dynamics simulation; ultrasonic radiation; Chitosan; fosforečnany vápenaté; biomimetic mineralization; Biomimetic Materials; koncentrace vodíkových iontů; chitosan; Molecular Dynamics Simulation; Hydrogen-Ion Concentration; octacalcium phosphate